2017
DOI: 10.1038/srep43829
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 ameliorates acute lung injury in influenza virus infection

Abstract: Interleukin 6 (IL-6) is involved in innate and adaptive immune responses to defend against pathogens. It also participates in the process of influenza infection by affecting viral clearance and immune cell responses. However, whether IL-6 impacts lung repair in influenza pathogenesis remains unclear. Here, we studied the role of IL-6 in acute influenza infection in mice. IL-6-deficient mice infected with influenza virus exhibited higher lethality, lost more body weight and had higher fibroblast accumulation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
119
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(122 citation statements)
references
References 44 publications
(48 reference statements)
1
119
0
Order By: Relevance
“…However, suppression but not depletion of the pro-inflammatory IL-1 family and IL-6 have been shown to have a therapeutic effect in many inflammatory diseases, including viral infections for instance, Mice lacking IL-1 signaling expression, elevated viral replication of coronavirus [72]. In addition, IL-6-deficient mice infected with influenza virus exhibited a higher lethality, more body weight loss and had higher fibroblast accumulation and lower extracellular matrix (ECM) turnover in the lungs than their wild-type counterparts [73]. The inflammasome, a cytosolic protein complex that mediates the processing and secretion of pro-inflammatory cytokines, is one of the first responders during viral infection.…”
Section: Ozone Therapy and Cytoprotectionmentioning
confidence: 99%
“…However, suppression but not depletion of the pro-inflammatory IL-1 family and IL-6 have been shown to have a therapeutic effect in many inflammatory diseases, including viral infections for instance, Mice lacking IL-1 signaling expression, elevated viral replication of coronavirus [72]. In addition, IL-6-deficient mice infected with influenza virus exhibited a higher lethality, more body weight loss and had higher fibroblast accumulation and lower extracellular matrix (ECM) turnover in the lungs than their wild-type counterparts [73]. The inflammasome, a cytosolic protein complex that mediates the processing and secretion of pro-inflammatory cytokines, is one of the first responders during viral infection.…”
Section: Ozone Therapy and Cytoprotectionmentioning
confidence: 99%
“…Specifically, Dienz and colleagues (37) reported that IL-6 2/2 mice succumbed to sublethal doses of influenza A H1N1 in association with apoptosis of antiviral neutrophils in the lung, whereas Lauder and colleagues (38) found that infection of IL-6 2/2 mice with influenza A H1N1 resulted in infiltration of the lungs with monocytes in association with progression to pulmonary edema and respiratory distress due to an inefficient antiviral T cell response. Subsequent studies that focused on the roles of CD4 + T cells, cytotoxic CD8 + T cells, and IL-27, IL-21, and Ab production as well as lung repair mechanisms (39)(40)(41)(42) all identified IL-6 as a protective factor in acute influenza infection.…”
mentioning
confidence: 99%
“…In many studies, IL-6 has been shown to increase with exposure to any insult causing acute lung injury to maintain the homeostasis of the inflammatory response [3638]. The increase in G-CSF and eotaxin along with the increase in CD4 cells in BALF suggest that acute exposure may be leaning toward the Th2 pathway, implicating potential eosinophilic pneumonia with prolonged exposure [39–41].…”
Section: Resultsmentioning
confidence: 99%